Functional characterisation of a tropine-forming reductase gene from Brugmansia arborea, a woody plant species producing tropane alkaloids. (July 2016) - Qiang, Wei; Xia, Ke; Zhang, Qiaozhuo; Zeng, Junlan; Huang, Yuanshe; Yang, Chunxian; Chen, Min; Liu, Xiaoqiang; Lan, Xiaozhong; Liao, Zhihua
Graphical abstract: BaTRI catalysed tropinone reduction at pH 6.4 and tropine oxidation at pH 9.4. The expression of BaTRI was found in all the examined organs, while the other known TRI genes of herbal plants are usually expressed in roots. Highlights: Brugmansia arborea is a woody plant species predominantly producing scopolamine. The expression profile of BaTRI showed no root specificity. BaTRI catalysed tropinone reduction at pH 6.4 and tropine oxidation at pH 9.6. BaTRI had higher tropinone reduction efficiency than DsTRI. Abstract: Brugmansia arborea is a woody plant species that produces tropane alkaloids (TAs). The gene encoding tropine-forming reductase or tropinone reductase I (BaTRI) in this plant species was functionally characterised. The full-length cDNA of BaTRI encoded a 272-amino-acid polypeptide that was highly similar to tropinone reductase I from TAs-producing herbal plant species. The purified 29 kDa recombinant BaTRI exhibited maximum reduction activity at pH 6.8–8.0 when tropinone was used as substrate; it also exhibited maximum oxidation activity at pH 9.6 when tropine was used as substrate. The K m, V max and K cat values of BaTRI for tropinone were 2.65 mM, 88.3 nkat mg −1 and 2.93 S −1, respectively, at pH 6.4; the K m, V max and K cat values of TRI from Datura stramonium (DsTRI) for tropinone were respectively 4.18 mM, 81.20 nkat mg −1 and 2.40 S −1 at pH 6.4. At pH 6.4, 6.8 and 7.0, BaTRI had a significantly higher activity than DsTRI. Analogues of tropinone, 4-methylcyclohexanone and 3-quinuclidinone hydrochloride, were also used to investigate the enzymatic kinetics of BaTRI. The K m, V max and K cat values of BaTRI for tropine were 0.56 mM, 171.62 nkat.mg −1 and 5.69 S −1, respectively, at pH 9.6; the K m, V max and K cat values of DsTRI for tropine were 0.34 mM, 111.90 nkat mg −1 and 3.30 S −1, respectively, at pH 9.6. The tissue profiles of BaTRI differed from those in TAs-producing herbal plant species. BaTRI was expressed in all examined organs but was most abundant in secondary roots. Finally, tropane alkaloids, including hyoscyamine, anisodamine and scopolamine, were detected in various organs of B. arborea by HPLC. Interestingly, scopolamine constituted most of the tropane alkaloids content in B. arborea, which suggests that B. arborea is a scopolamine-rich plant species. The scopolamine content was much higher in the leaves and stems than in other organs. The gene expression and TAs accumulation suggest that the biosynthesis of hyoscyamine, especially scopolamine, occurred not only in the roots but also in the aerial parts of B. arborea .